2019
DOI: 10.1186/s40425-019-0701-2
|View full text |Cite|
|
Sign up to set email alerts
|

Colorectal cancer cell-derived CCL20 recruits regulatory T cells to promote chemoresistance via FOXO1/CEBPB/NF-κB signaling

Abstract: Background Colorectal cancer (CRC) is one of the most common forms of cancer worldwide. The tumor microenvironment plays a key role in promoting the occurrence of chemoresistance in solid cancers. Effective targets to overcome resistance are necessary to improve the survival and prognosis of CRC patients. This study aimed to evaluate the molecular mechanisms of the tumor microenvironment that might be involved in chemoresistance in patients with CRC. Methods We evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(130 citation statements)
references
References 53 publications
(48 reference statements)
1
129
0
Order By: Relevance
“…6K, S7A). Studies of other cancers have demonstrated that CCL20 signaling can promote tumor growth, invasiveness and chemoresistance (Lee et al, 2017;Lu et al, 2017;Walch-Ruckheim et al, 2015) by recruitment of Tregs and/or T H 17 cells (Walch-Ruckheim et al, 2015;Wang et al, 2019). CCL20 expression on the protein level was confirmed with ELISA using plasma from different bone marrow fractions (Supplementary Table 6).…”
Section: Coordination Between Myeloid and Lymphoid Compartmentsmentioning
confidence: 79%
“…6K, S7A). Studies of other cancers have demonstrated that CCL20 signaling can promote tumor growth, invasiveness and chemoresistance (Lee et al, 2017;Lu et al, 2017;Walch-Ruckheim et al, 2015) by recruitment of Tregs and/or T H 17 cells (Walch-Ruckheim et al, 2015;Wang et al, 2019). CCL20 expression on the protein level was confirmed with ELISA using plasma from different bone marrow fractions (Supplementary Table 6).…”
Section: Coordination Between Myeloid and Lymphoid Compartmentsmentioning
confidence: 79%
“…According to RECIST 1.1 criteria, CRC patients were divided into Sensitive-CRC group (containing Complete Response, Partial Response and Stable Disease) and Resistant-CRC group (Progressive Disease). 25 This research had granted approval by the Ethics Committee of The Sixth Affiliated Hospital of Sun Yat-sen University.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…For example, cells that die from chemotherapy release molecules that regulate the immune response, stimulate angiogenesis, alter the physicochemical parameters of the tumor microenvironment, or activate cellular invasion [216]. An immunosuppressive effect has been shown for molecules released by dying cancer cells, e.g., secreted CCL20 recruits regulatory T cells via the FOXO1/CEBPB/NF-κB signaling [217]; sphingosine-1 phosphate activates and polarizes of tumor-associated macrophages into M2 macrophages. These M2 macrophages secrete anti-inflammatory IL-10, and PGE2 supporting the migration of endothelial cells and angiogenesis [218].…”
Section: Communication Between Cancer Cells and Surrounding Stromal Cmentioning
confidence: 99%